FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN WARGA PADA MASA PANDEMI COVID-19 TAHUN 2021 DI KECAMATAN SUKMAJAYA KOTA DEPOK - Aliefia Dinda Fortuna; Milla Evelianti Saputri; Tommy Jemmy Farancius Wowor (Universitas Sam Ratulangi, 2022)
Background: The conditions that occurred during the COVID-19 pandemic had a psychological effect on the community, such as high anxiety which could make the body's immune system decrease. Aim: to identify the factors related to the anxiety level during covid-19 pandemic in Tirtajaya village, Sukmajaya sub-district, Depok City. Methods: cross sectional study was conducted and anlayzed by using chi-square to identify the relationship between variables. There were 70 respondents through purposive sampling, Self- Rating Anxiety Scale (SRAS) was used as an instrument in the study. Results: showed that there was a relationship between age (p-value =0.020), gender (p-value= 0.029), education level (p-value= 0.029), employment status (pvalue = 0.004). and the environment (p-value =0.015) with the level of anxiety during the COVID-19 pandemic. Conclusion: In this study, women in the age group of 17-25 years, the last education level is senior high school, not working, and being in an unhealthy environment were more dominant in experiencing anxiety.Keywords: Anxiety; COVID-19; Psychological effects